Proceedings of the 11th Conference on Advances in Computer Entertainment Technology 2014
DOI: 10.1145/2663806.2663821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of orchestrated, game-based learning in virtual environments for informal education

Abstract: In informal learning spaces employing digital content, such as museums, visitors often do not get adequate exposure to content, or they passively receive instruction offered by a museum docent to the whole group. This research aims to identify which elements of co-located group collaboration, virtual environments, and serious games can be leveraged for an enhanced museum learning and entertaining experience. We developed C-OLiVE, an interactive virtual environment supporting tripartite group collaboration, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 25 publications
1
30
0
1
Order By: Relevance
“…So, the capability for virtual environments shared by multiple participants has been around for a long time, supported by many platforms, and realized in massive online systems such as Second Life, although typically non-immersively. The work by Apostolellis and Bowman (2014) is a good recent illustration of collaboration in a learning context that was realized with screen-based displays. The early days of research in this area, apart from the technical issues of how to build systems, concentrated on exploiting the capabilities of VR to improve remote collaboration beyond what might be possible even in face-to-face communications -for example, the type of work reported in Benford and Fahlén (1993) and Koleva et al (2001).…”
Section: Shared Virtual Environmentsmentioning
confidence: 99%
“…So, the capability for virtual environments shared by multiple participants has been around for a long time, supported by many platforms, and realized in massive online systems such as Second Life, although typically non-immersively. The work by Apostolellis and Bowman (2014) is a good recent illustration of collaboration in a learning context that was realized with screen-based displays. The early days of research in this area, apart from the technical issues of how to build systems, concentrated on exploiting the capabilities of VR to improve remote collaboration beyond what might be possible even in face-to-face communications -for example, the type of work reported in Benford and Fahlén (1993) and Koleva et al (2001).…”
Section: Shared Virtual Environmentsmentioning
confidence: 99%
“…Accumulating evidence suggests that unguided instruction during discovery learning often proves to be less effective as compared to guided instruction [19]. Since in our previous study [3] unguided students showed reduced learning gains as a result of a poorer game experience, in the current study we also evaluated the impact of facilitation during collaborative game play.…”
Section: Related Workmentioning
confidence: 95%
“…Following up on our previous study in the US [3], in this paper we report our findings from our second experiment with a different population, in a museum space in Greece. Our hypothesis was that culturally driven prior exposure to and interest in the subject would improve game experience and consequently learning, as these two variables were shown to be positively correlated in our first study.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations